Effects and Prevention of Soil Compaction in Conventional Tillage: Challenges and Solutions - Hetz, Edmundo; Reina-Castro, Lizardo; Reyna-Bowen, José Lizardo (REVISTA TERRA LATINOAMERICANA, 2025)
The objective of this research was to analyze the mechanisms of soil compaction under conventional tillage, contributing to the understanding of its characterization, prevention, reduction, and elimination when generated by agricultural machinery traf fic, which negatively af fects seed germination, root development, and consequently, crop yield. A systematic literature review was conducted, analyzing forty-four scientific articles published over the last 20 years and complemented with information from relevant textbooks. The search was performed in databases such as Google Scholar, Scopus, ScienceDirect, SpringerLink, Wiley Online Library, Taylor & Francis Online, Academia.edu, and ResearchGate. The results describe soil compaction, its causal factors and ef fects, and include a quantification of the loads transported by agricultural machinery and the pressures exerted at the tire–soil interface. Various prevention and mitigation strategies are presented, ranging from machinery selection and optimized operation (considering ballasting, tire types, and the incorporation of precision agriculture) to the implementation of appropriate tillage systems. It is concluded that, although compaction is inherent to mechanized agriculture, a comprehensive and proactive approach is essential for its ef fective management, making it crucial to simultaneously optimize machinery–soil contact pressure and improve soil load-bearing capacity and structure to ensure sustainable agricultural production.